EMOTIONAL INTELLIGENCE AND RESILIENCE - Vasquez, Karla (Acta Scientiae et Intellectus, 2024)
The following paper explores the concepts of emotional intelligence (EI) and resilience. There is some disagreement and debate about the meaning and definition of both constructs. EI as a construct refers to a person’s ability to recognize their own emotions as well as the emotions of others. Resilience refers to a person’s ability to resist the negative consequences related to stressful and traumatic events. Despite the differences in how the constructs are defined, there is general agreement that there is a direct relationship between EI and resilience. Generally speaking, researchers and academics agree that higher levels of EI help individuals to develop greater resilience. By the same token, there is general agreement that lower levels of EI lead to an individual’s diminished ability to develop resilience. There are certain individuals who seem able to endure stressful life events or traumatic circumstances without permanent debilitation. On the other hand, there are individuals who suffer seemingly less stressful events or smaller moments of trauma, but are greatly damaged by these incidents. The questions of how individuals develop EI and resilience and why certain individuals are more resilient than others are dynamic and complex.